Spinal Cord Involvement in Brachial Plexus Injury - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 2004)
The role of spinal cord plasticity after birth injury and recovery from obstetric brachial plexus lesions was investigated in newborn rats with selective crush injury to spinal roots C5 and C6, in a study at University Clinics of Vienna School of Medicine, Austria.